The law and politics of the Kosovo advisory opinion - Milanović, Marko (Oxford University Press, 2015)
This is an edited collection of essays on various aspects of the 2010 Kosovo Advisory Opinion of the International Court of Justice. The main theme of the book is the interplay between law and politics regarding Kosovo's independence generally and the advisory opinion specifically. The book tells the story of the case, places it within its broader political context, and so attempts to advance our understanding of how such cases are initiated, litigated and decided, and what broader purposes they may or may not serve.
Includes bibliographical references and index
Keywords: International Court of Justice; Kosovo (Republic) -- History -- 2008-; Aufsatzsammlung; Internationaler Gerichtshof; Unabhängigkeit; Kosovo